“If two people say you are drunk, you better go to bed”: Interview with Gyula Gyulyás. - Győri, Zsolt (Panoptikum, 2024)
This article explores bio documentary cinema, an often overlooked biographic genre that, unlike its “big brother,” the biopic focusing on the lives, achievements, and legacy of people from the past, prefers to investigate living people through interviews and other forms of interaction. In order to understand the challenges, methods and human dynamic shaping talking heads documentaries, the article prioritizes the first-hand experience of the filmmaker, more specifically, that of Gyula Gulyás, a Hungarian director of documentaries for over five decades. After a general introduction to his career path, preferred topics and shared interests with local and regional documentary filmmakers, the interview covers areas relevant to the biographic documentary such as generic labels, professional standards and the usefulness of cinematic portraits for academic research, choice of subject, methods of interviewing and structuring recorded material, moral responsibility and intimacy as a well as general and specific questions about financing and distributing biographic documentaries, their reception, and the struggle with political and non-political censorship